Perilaku Pemakaian Alat Pelindung Diri (APD) dengan Gejala ISPA pada Pengguna Jalan Raya Pasca Erupsi Gunung - Fransisco Godinho Pereira; Ninuk Dian Kurniawati; Elida Ulfiana (Journal of Telenursing (JOTING), 2023)
This study aims to determine the relationship between the behavior of using PPE and symptoms of ARI on road users on Dhoho road after the eruption of Mount Kelud in Kediri City. The method used is quantitative analysis with a cross-sectional approach. The sampling technique uses Accidental Sampling, with the sample being road users in Jalan Dhoho, Kediri City. Data collection was carried out using a questionnaire and conservation sheets which were then analyzed using the chi-square test. The results showed that the p-value obtained was 0.005, meaning that there was a relationship between PPE usage behavior and ARI symptoms in road users on Dhoho road after the eruption of Mount Kelud in Kediri City. In conclusion, wearing a mask as PPE during the Kelud eruption can reduce the incidence of ARI symptoms because it prevents particles or dust from entering the respiratory tract. Keywords: Personal protective equipment (PPE), ARI symptoms, post-eruption